1994
DOI: 10.1002/ar.1092400105
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic and histochemical studies of the mononuclear odontoclast of the human

Abstract: The present study concludes that cells with ruffled borders and clear zones observed by transmission electron microscopy can be identified as odontoclasts or osteoclasts irrespective of the number of nuclei.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 58 publications
3
23
0
1
Order By: Relevance
“…The significance of these structures will be considered here. It has been reported that TRAP activity is a specific marker for human odontoclasts (Domon et al, 1994;Sahara et al, 1996). This indicates that the TRAP-positive structures with a TUNEL-positive nucleus as shown in this study are apoptotic odontoclasts.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The significance of these structures will be considered here. It has been reported that TRAP activity is a specific marker for human odontoclasts (Domon et al, 1994;Sahara et al, 1996). This indicates that the TRAP-positive structures with a TUNEL-positive nucleus as shown in this study are apoptotic odontoclasts.…”
Section: Discussionsupporting
confidence: 77%
“…On the resorbing surfaces there were mononuclear odontoclasts with resorptive ability, and they also participate in the tooth resorption (Domon et al, 1994(Domon et al, , 1997(Domon et al, , 1998. Therefore, detailed observations of the resorbing surfaces of human deciduous teeth under physiological root resorption suggest a potential site for encountering apoptosis of odontoclasts in normal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These reports disregarded the presence of mononuclear osteoclasts which were observed in serial sections based on criteria of both acid phosphatase activity and resorptive lacunae (Kaye, 1984) or odontoclasts because their presence was not proven precisely. Previously, we have demonstrated the presence of mononuclear osteoclasts with ruffled borders in vitro (Domon and Wakita, 1991) and mononuclear odontoclasts in vivo (Domon et al, 1994), and investigated the distribution of number of nuclei per human odontoclast, and reported that 93.8% of cells had 10 or fewer, including mononucleus (Domon et al, 1997). These reports indicate that the distribution of nuclei in osteoclasts or odontoclasts varies little in mammals.…”
Section: Introductionmentioning
confidence: 74%
“…On human deciduous teeth, such a situation has not been observed and the resorbed surfaces are not filled with odontoclasts (Domon et al, 1994). It is reported that mammalian osteoclasts alternate resorption with migration and this alternation makes the resorbed surfaces smooth (Jones et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…They are considered to be of the same cell types as osteoclasts in their ultrastructural and histochemical features, and to be capable of resorting all dental hard tissues (SASAKI et al, 1988(SASAKI et al, . 1989TANAKA et al, 1990;MATSUDA, 1992;SASAKI and UENO-MATSUDA, 1992;SAHARA et al, 1992SAHARA et al, , 1994SAHARA et al, , 1996DOMON et al, 1994;YAWAKA et al, 1995). The resorption first begins on the root surface and subsequently proceeds inward to the root canal and coronal dentin wall, the process being regarded as the internal resorption (FURSETH, 1968;SOSKOLNE and BIMSTEIN, 1977;ROLLING, 1981;ISHIKURA, 1991;SA-HARA et al,1992;YAWAKA et al, 1995).…”
mentioning
confidence: 99%